A Study of Nusantara Islam in the Context of Multiculturalism in Indonesia - Burhanuddin, Ahmad; Muzayyin, Ahmad; iswanto, Juni (Westscience Press, 2025)
This study will focus on the peculiarity of Nusantara Islam amidst the setting of Indonesian multiculturalism by studying the content analytically based on 21 documents indexed by Scopus. For that reason, Islam is seen harmoniously merged within the variances of the Indonesia cultural setting for religious tolerance to meet societal peaceful coexistence. The findings prove Nusantara Islam is inclusive, and flexible, and hence has emerged pivotal in unifying the highly fractionalized populace along unifying bonds of unity over diversity. It struggles for sustainability amidst the growing transnational ideologies, globalization, and digital dissemination of radical discourses. This paper underlines the value of Nusantara Islam as a model of religious moderation and provides recommendations on how to meet contemporary challenges. The research enriches the body of knowledge dealing with the interrelationship between religion and multiculturalism in ways that benefit the global discourses of interfaith harmony and cultural pluralism.